2016
DOI: 10.1093/ageing/afw150
|View full text |Cite
|
Sign up to set email alerts
|

ARB users exhibit a lower fracture incidence than ACE inhibitor users among older hypertensive men

Abstract: In older hypertensive men, ARBs use was associated with lower incidence of non-vertebral fracture than ACE inhibitors or CCBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…Among numerous drugs used for HPI-related diseases many are well known to contribute to OP/OFs. In regard to OP, these include corticosteroids, antidepressants (especially, selective serotonin- and serotonin-norepinephrine reuptake inhibitors), glitazones, opioids, benzodiazepines, antipsychotics, antiparkinsonian drugs, antiepileptics, PPIs, H2RA, thyroxine, furosemide, aromatase inhibitors, gonadotropin releasing hormone (GnRH) agonists, whereas hormone replacement therapy with estrogen, thiazides, angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs), spironolactone, beta-blockers, statins, antihistamines, metformin, sulphonylureas, glucagon-like peptide-1 receptor agonists (liraglutide) and nitrates have shown an osteoprotective effect [ 316 , 521 , 522 , 523 , 524 , 525 , 526 , 527 , 528 , 529 , 530 , 531 , 532 , 533 , 534 , 535 , 536 , 537 , 538 , 539 , 540 , 541 , 542 , 543 , 544 , 545 , 546 , 547 , 548 , 549 , 550 , 551 , 552 , 553 , 554 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Among numerous drugs used for HPI-related diseases many are well known to contribute to OP/OFs. In regard to OP, these include corticosteroids, antidepressants (especially, selective serotonin- and serotonin-norepinephrine reuptake inhibitors), glitazones, opioids, benzodiazepines, antipsychotics, antiparkinsonian drugs, antiepileptics, PPIs, H2RA, thyroxine, furosemide, aromatase inhibitors, gonadotropin releasing hormone (GnRH) agonists, whereas hormone replacement therapy with estrogen, thiazides, angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs), spironolactone, beta-blockers, statins, antihistamines, metformin, sulphonylureas, glucagon-like peptide-1 receptor agonists (liraglutide) and nitrates have shown an osteoprotective effect [ 316 , 521 , 522 , 523 , 524 , 525 , 526 , 527 , 528 , 529 , 530 , 531 , 532 , 533 , 534 , 535 , 536 , 537 , 538 , 539 , 540 , 541 , 542 , 543 , 544 , 545 , 546 , 547 , 548 , 549 , 550 , 551 , 552 , 553 , 554 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…An alternate explanation would be an improper selection of a priori falsification endpoints given limited studies suggesting lower risk of fracture with ARB than ACEI therapy. 58 However, this has not been seen with UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Ruths et al in their large cohort study in Norway showed that all kinds of hypertension medication may prevent hip fracture except loop diuretics and ACEI in patients older than 80s. And another cohort study in the United States by Kwok et al, [ 34 ] on older hypertensive men reported that ARB users had lower risk of fracture than ACEI users.…”
Section: Discussionmentioning
confidence: 99%